Institutional Agonism: Axel Honneth's Radical Democracy*. Issue 1 (2nd January 2017) - Lysaker, Odin
ABSTRACT: Axel Honneth may be criticised for reducing political philosophy to moral psychology. In what follows, I argue that if his theory of recognition is reframed as one of democracy, quite another picture will appear. To do this, I systematically reconstruct Honneth's stance as a multidimensional version of radical democracy. The question I discuss is the manner in which this framework combines the three dimensions of democratic deliberation, culture, and conflict. I then discuss Honneth's picture from both a deliberative and agonistic viewpoint. How one understands the way in which he combines the abovementioned dimensions is dependent upon which one of these two approaches one may choose. I claim that when taken together, these three dimensions form the grounding of a radical-democratic understanding of a struggle for recognition, which I term institutional agonism.